The Patterns of Recurrences in Idiopathic Benign Paroxysmal Positional Vertigo and Self-treatment Evaluation - Kim, Hyo-Jung; Kim, Ji-Soo (Frontiers in Neurology, 2017)
Background and Objectives: Self-administration of canalith repositioning procedures (CRP) may be instructed easily for recurred benign paroxysmal positional vertigo (BPPV) if each patient has a predilection for a specific canal and the type of recurred BPPV can be predicted from that observed during the previous event. Methods: We analyzed the involved side (right, left, and bilateral) and affected canal (posterior, geotropic horizontal, apogeotropic horizontal, anterior, and mixed) in 224 pairs of consecutive attacks of BPPV from 167 patients at the Dizziness Clinic of Seoul National Bundang Hospital from 2003 to 2017. The recurrence was defined when patients redeveloped positional vertigo and nystagmus at least one week after resolution of the previous positional vertigo and nystagmus. Results: During the initial attack, the involved canals were posterior in 134 (59.8%), geotropic horizontal in 53 (23.7%), apogeotropic horizontal in 27 (12.1%), anterior in 5 (2.2%), and mixed in 5 (2.2%). The right ear was affected in 132 (58.9%), the left ear in 90 (40.2 %), and both ears in 2 (0.9%). During the recurrences, the proportion of involved canals (p=0.9738) and affected side (p=0.7966) did not differ from those during the former event (Chi-squared test). Only 24% of the patients showed the recurrence in the same canal on the same side. Conclusion: The pattern of recurrences was usually discordant in patients with BPPV. Education for self-administration of a specific CRP based on the type of BPPV during the previous event may be of limited clinical utility in treating this frequently recurrent disorder.